Trunk rotation, spinal deformity and appearance, health-related quality of life, and treatment adherence: Secondary outcomes in a randomized controlled trial on conservative treatment for adolescent idiopathic scoliosis - Marlene Dufvenberg; Anastasios Charalampidis; Elias Diarbakerli; Birgitta Öberg; Hans Tropp; Anna Aspberg Ahl; Hans Möller; Paul Gerdhem; Allan Abbott (PLoS ONE, 2025)
Objective To explore secondary outcomes at endpoint comparing treatments with adequate self-mediated physical activity combined with either night-time brace (NB), scoliosis-specific exercise (SSE), or adequate self-mediated physical activity alone (PA) in Adolescent Idiopathic Scoliosis (AIS). Methods A longitudinal, prospective, multicenter RCT was conducted including 135 girls/boys, Cobb angle 25–40°, 9–17 years, and ≥1-year remaining growth were randomly allocated into NB, SSE, or PA group. Endpoint was curve progression of ≤6° (success) at skeletal maturity or >6° (failure). Outcomes included angle of trunk rotation (ATR), major curve Cobb angle, Spinal Appearance Questionnaire (pSAQ), Scoliosis Research Society-22r (SRS-22r), EQ-5Dimensions Youth 3Levels (EQ-5D-Y-3L), and EQ-Visual-Analogue-Scale (EQ-VAS), adherence to treatment and International Physical Activity Questionnaire (IPAQ-SF). Results At endpoint, 122 patients were analyzed per protocol, mean age 12.7 (±1.4) years, and mean Cobb angle 31° (±4.3). A significant difference in change for ATR favored NB group compared to SSE group -2.0º (95% CI -3.7 to -0.3). EQ-5D-Y-3L dimensions showed a significant difference in change with decrease in mobility (p=0.031), and usual activities (p=0.003) for SSE compared to NB and PA groups. Treatment adherence was adequate but slightly better in NB and PA groups compared to SSE on self-report (p=0.012), and health care provider (HCP) report was better in PA compared to SSE group (p=0.013). Higher motivation and capability explained 53% of the variability and gave better odds for higher adherence (OR = 11.12, 95% CI = 1.5 to 34.4; OR = 7.23, 95% CI = 2.9 to 43.3), respectively. Conclusions Night-time brace, scoliosis-specific exercise or physical activity interventions for adolescents with idiopathic scoliosis showed small differences between groups in trunk rotation, spinal deformity and appearance, health-related quality of life, and treatment adherence but not likely reaching clinical relevance.